2014
DOI: 10.17221/7817-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medium chain fatty acids (MCFA) and probiotic (Enterococcus faecium) supplementation on the growth performance, digestibility and blood profiles in weanling pigs

Abstract: ABSTRACT:The objective of the present study was to evaluate the effects of MCFA and probiotic (Enterococcus faecium DSM 7134) supplementation on growth performance, nutrient digestibility, blood profiles, faecal score, excreta microbiota, and excreta noxious gas emission in weanling pigs. A total of 140 weanling pigs [(Yorkshire × Landrace) × Duroc] were allotted to four treatments groups of seven replicates/treatment and five pigs/replicate. The four experimental diets included: CON diet (basal diet); T1 (CON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Small differences in blood levels of cholesterol in piglets were found by Mohana Devi and Kim [42] and by Allee et al [43] after supplementing feed with MCFA. In an experiment on broilers, Wang et al [44] found that total and LDL cholesterol levels in the blood of birds decreased when the content of coconut oil in feed increased.…”
Section: Effect Of Piglet Feeding On Intestinal Development and Healtmentioning
confidence: 80%
“…Small differences in blood levels of cholesterol in piglets were found by Mohana Devi and Kim [42] and by Allee et al [43] after supplementing feed with MCFA. In an experiment on broilers, Wang et al [44] found that total and LDL cholesterol levels in the blood of birds decreased when the content of coconut oil in feed increased.…”
Section: Effect Of Piglet Feeding On Intestinal Development and Healtmentioning
confidence: 80%
“…However, our data indicated no influences on RBC, WBC, and lymphocyte when diets were incorporated with Bacillus probiotic, which is in agreement with our previous studies (Chen et al, 2005;2006;Yan and Kim, 2011). According to Mohana Devi and Kim (2014), probiotic supplementation showed a significant (P<0.05) effect on glucose concentration in weanling pigs. Similarly, our result showed that the Bacillus probiotic had a significant (P<0.05) effect on glucose level during the entire experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…A further element that can be mentioned in favour of the inclusion of BSF prepupae in poultry and pig feed, given their richness in C12:0, is the faster and more efficient absorption and metabolism of medium chain fatty acids (MCFA) compared to long chain fatty acids (LCFA) and their nutraceutical potential . Skrivanova et al showed that C12:0 had the highest activity against Clostridium perfringens as compared to other MCFA.…”
Section: Discussionmentioning
confidence: 99%